Predicting malignant and benign brain tumor using image processing - Saxena, Rishabh; Johri, Aakriti; Deep, Vikas; Sharma, Purushottam (International Journal of Engineering and Technology, 2018)
Brain is the most important and versatile organ of the human body. One of the most deadly diseases that damage the brain is the accumulation of unwanted and deadly cells near the curvature of brain known as brain tumor. There are two types of brain tumor namely malignant and benign. Malignant is a cancerous tumor and benign is a non cancerous tumor. Primarily brain tumor grows in the brain tissue. The project uses MATLAB to develop a prediction system which uses original hospital brain MRI to predict the brain tumor. Project uses digital image processing to predict the brain tumor. The use of certain image mining algorithms helps in predicting the correct spot and area of brain tumor by image segmentation. The procedure starts with uploading MRI image of human brain, forward by the pre-processing of the image.Â Â